2020
DOI: 10.1002/jwmg.21925
|View full text |Cite
|
Sign up to set email alerts
|

Northern Bobwhite Non‐Breeding Habitat Selection in a Longleaf Pine Woodland

Abstract: Efforts to halt the decline of the northern bobwhite (Colinus virginianus; bobwhite) across its distribution have had limited success. Understanding bobwhite habitat requirements across the annual cycle and at varying scales is essential to aid efforts to conserve bobwhites. We monitored radio-tagged bobwhites from 2016 to 2018 on a 165-km 2 portion of Fort Bragg Military Installation in the Sandhills physiographic region of North Carolina, USA, to determine factors influencing non-breeding bobwhite habitat se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
0
3
1
Order By: Relevance
“…Selection for nesting in areas with greater woody understory cover, including shrubs and regenerating trees, likely is indicative of selection for the most limiting nest cover components on Fort Bragg. Basal area or tree density is thought to underlie habitat quality for bobwhite across its range (Fies et al 1992, Brennan et al 1998, Rosche et al 2019, Kroeger et al 2020, Hannon et al 2021), though we documented non‐significant trends of selecting lower basal area for nest sites in our study. Midstory and overstory tree cover competes for sunlight with understory plants, and thus a lower basal area is more beneficial for bobwhite because it allows adequate sunlight required for development of the understory that provides nesting cover.…”
Section: Discussioncontrasting
confidence: 65%
“…Selection for nesting in areas with greater woody understory cover, including shrubs and regenerating trees, likely is indicative of selection for the most limiting nest cover components on Fort Bragg. Basal area or tree density is thought to underlie habitat quality for bobwhite across its range (Fies et al 1992, Brennan et al 1998, Rosche et al 2019, Kroeger et al 2020, Hannon et al 2021), though we documented non‐significant trends of selecting lower basal area for nest sites in our study. Midstory and overstory tree cover competes for sunlight with understory plants, and thus a lower basal area is more beneficial for bobwhite because it allows adequate sunlight required for development of the understory that provides nesting cover.…”
Section: Discussioncontrasting
confidence: 65%
“…Managers should focus habitat features that can protect bobwhites from these sources. Woody understory cover is well documented to be beneficial to bobwhites and other galliformes during the nonbreeding season (Roseberry et al 1964, Roseberry and Klimstra 1984, Janke and Gates 2013, Warren et al 2013, Kroeger et al 2020). Furthermore, in an associated study, we found that bobwhites selected habitat during the nonbreeding season with increased visual obstruction (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Visual obstruction as influenced by the structure of vegetation may determine occupancy and use of an area by various wildlife species (Swanson et al 1999, Lashley et al 2015, Kroeger et al 2020). Visual obstruction and habitat use by certain wildlife species may vary as vegetation type, density, and height changes (Winter et al 2005).…”
Section: Discussionmentioning
confidence: 99%